THE INFLUENCE OF COMPETENCE AND WORKLOAD ON ASN PERFORMANCE IN THE NORTH SUMATRA ENVIRONMENT AND FORESTRY SERVICE - Isma Zulaiha; Yeni Absah; Prihatin Lumbanraja (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
The North Sumatra LHK Service has a very complex and crucial role. The North Sumatra LHK Service must monitor and maintain forest sustainability, prevent forest encroachment, and support forest and land rehabilitation activities. The performance that occurs in the North Sumatra Forestry and Environment Service is the lack of skills development programs to overcome the lack of competency that employees may have. This condition can cause a decline in performance in the long term. Then, excessive workload for employees is given responsibilities or tasks that exceed their capacity, which results in a decrease in the quality of their performance. This research aims to determine and analyze the influence of competency and workload on ASN performance in the North Sumatra Environment and Forestry Service. The population in this study is the permanent employees of the Environment and Forestry Service of North Sumatra Province, which as of August 2023 are 629 employees. The total sample was 126 employees from the Environment and Forestry Service of North Sumatra Province. The sampling method refers to the simple random sampling technique. The data collection technique in this research is using Multiple Linear Regression Analysis. The results of this research are that competency has a positive and significant effect on ASN performance. Workload has a positive and significant effect on ASN performance.